2013
DOI: 10.1111/lam.12113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the germination kinetics of individual Bacillus subtilis spores treated with hydrogen peroxide or sodium hypochlorite

Abstract: Significance and Impact of the Study: This work shows that with Bacillus subtilis spore populations in which approximately 95% of individual spores were killed by several oxidizing agents, >95% of the spores in these populations germinated with nutrients, albeit slowly. This is important, as assay of an early germination event, release of dipicolinic acid, has been suggested as a rapid assay for spore viability and would give false-positive readings for the level of the killing of oxidizing agent-treated spore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
5
30
0
Order By: Relevance
“…S8A in the supplemental material). Second, it has been shown that certain stresses, such as pH and oxidative stresses, significantly extend the lag time for germination of Bacillus spores (55,56). We have observed extended lag phases for growth of MIT0214 under 1 atm CO 2 compared to 1 atm N 2 (see Fig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…S8A in the supplemental material). Second, it has been shown that certain stresses, such as pH and oxidative stresses, significantly extend the lag time for germination of Bacillus spores (55,56). We have observed extended lag phases for growth of MIT0214 under 1 atm CO 2 compared to 1 atm N 2 (see Fig.…”
Section: Discussionmentioning
confidence: 51%
“…First, germination frequencies under CO 2 headspaces are known to be significantly lower than those under aerobic or anaerobic nitrogen headspaces, with only 10 to 30% of B. cereus spores germinating under 1 atm CO 2 (55). Growth dynamics for isolate B. cereus MIT0214 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, DPA release from the I 2 ‐treated spores exposed to nutrient germinants is slower than that of untreated spores, as seen with B. subtilis spores treated with other oxidizing agents (Setlow et al . ). This slowed DPA release in germination conditions by I 2 ‐treated spores seems likely due in part due to inactivation of spores’ IM germinant receptors (GRs) that recognize the nutrient germinants (Setlow ), since the rate of germination with AGFK via the GerB and GerK GRs was decreased much more than with l ‐valine via the GerA GR, as reported for spores treated with another oxidizing agent (Setlow et al .…”
Section: Discussionmentioning
confidence: 97%
“…The results obtained in this study, for each microorganism, show that the inhibitory effect of the disinfectant is directly influenced by the exposure time; for this case, it is recommended to use the highlevel hydrogen peroxide-based disinfectant, STERIS, at a concentration of 2%, with a contact time of 5 min, as established by the producer. Several studies [10,[13][14][15], in which the microorganisms Bacillus subtilis, Pseudomonas aeruginosa, and Staphylococcus aureus were used as a control, showed that hydrogen peroxide is 100% effective against these microorganisms at a concentration of 3% with a time of 5 min contact for vegetative bacteria and more than 2 h for the sporulated microorganism. The same effect was achieved in the present study, compared with all the strains tested, with the same time but at a lower concentration of the product at 2%.…”
Section: Discussionmentioning
confidence: 99%